Potensi Energi Angin Pada Kawasan Pesisir Pantai untuk Menghasilkan Energi Listrik - Sari, Kamalia Zahra Ratna; ., Yushardi; ., Sudartik (CV. ITTC INDONESIA, 2023)
The purpose of this article research is to determine the potential of wind on the coast to produce electrical energy. Wind can be interpreted as air that moves due to temperature differences, both are hot temperatures and cold temperatures. The need for energy, especially electrical energy, in Indonesia is increasing and becoming an inseparable part of society's daily needs. From this background and problem formulation, a research study was carried out which focused on wind energy sources on the coast.